Electrical characterization and interface state density properties of the ITO/C70/Au Schottky diode - Yakuphanoğlu, Fahrettin (Amer Chemical Soc, 2007)
The electronic parameters and interface properties of the ITO/C-70/Au Schottky diode have been investigated by current-voltage characteristics. ITO/C-70/Au diode is a metal-insulator-semiconductor-type device. The ideality factor n and barrier height Ob values of the diode were found to be 1.29 and 0.88 eV, respectively. The diode shows a nonideal current-voltage behavior probably due to high probability of electron and hole recombination in the depletion region or occurrence of tunneling current or presence of an interfacial layer or series resistance. The obtained values are lower than equivalent values obtained previously without considering effect of the presence of interfacial layer. The density distribution of the interface states changes from 9.51 x 10(13) to 1.57 x 10(11) eV(-1) cm(-2).
Keywords: Current-Voltage Characteristics; Barrier; Dependence